Chemical composition and digestible energy of some feedstuffs determined with pigs in Malaysia - Kuan, K. K.; Mak, T. K.; Alimon, Abdul Razak; Farrell, D. J. (1982)
The gross energy and proximate composition of 18 feed ingredients were determined. Metabolism trials were conducted with growing castrated pigs to assess the apparent digestibi1ities of dry matter (DM), energy and crude protein of these feedstuffs. DM digestibi1ities ranged from 38.7% for palm oil sludge to 93.3% for brewers dried yeast. Digestible energy values on a DM basis, ranged from 8.86 MJ/kg for palm oi1 to 1J.IO MJ/kg for soya bean meal. Digestibi1ities of crude protein on a DM basis ranged from 49.2% for cocoa husk to 89.9% for fish meal. It was concluded that 6rowth studies should be conducted to determine the economic and nutritional worth of the agricultural by-products in pig diets.